Conference Report: Science and technology coming together to make a difference. (February 2012) - Needham, Shane; Johnson, Casey; Hayes, Roger; Lee, Mike
This annual meeting began in 1998 and was the first industry-led event to focus on the specific needs of industry researchers. The goal of Chemical and Pharmaceutical Structure Analysis is to provide an in-depth review of innovative technology and industry practices through open discussion of industry-related issues and needs. Education and specialized training are the foundation of all Chemical and Pharmaceutical Structure Analysis events – where technology and solutions meet.